Nutritional psychology and inflammatory bowel disease: a narrative review of gut-brain axis interactions - Horovitz, Omer (Frontiers in Nutrition, 2025)
This paper explores the intricate relationship between Inflammatory Bowel Disease (IBD) and psychopathology, with a particular focus on anxiety and depression. This narrative review synthesizes recent findings on how dietary factors and nutritional psychology influence the gut-brain axis in patients with inflammatory bowel disease. The bidirectional gut-brain axis, chronic inflammation, and psychological stress are all key contributors to the mental health burden in IBD patients. The paper reviews the physiological mechanisms linking IBD and psychiatric symptoms, particularly how inflammation and gut microbiota composition may influence mood disorders. It addresses the variability in psychiatric comorbidities across IBD subtypes (Crohn’s disease and ulcerative colitis) and highlights the challenges in standardized diagnosis and treatment. Emerging research on microbiome-based therapies, nutritional interventions, and personalized care approaches offers promising solutions for improving gastrointestinal and mental health outcomes. Integrating multidisciplinary care, involving gastroenterologists, psychiatrists, and dietitians, alongside advances in precision medicine, holds potential for developing more effective, individualized treatment strategies. However, challenges remain regarding variability in patient responses, methodological inconsistencies, and the need for standardized clinical protocols. The paper concludes by calling for further research to clarify these relationships and optimize treatment for IBD patients struggling with both physical and psychological health challenges.